2021
DOI: 10.1016/j.heliyon.2021.e08032
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of the most common neuropathies following knee injuries and reconstructive surgery – A narrative review

Abstract: The main nerves in the knee region are the tibial nerve, the common peroneal nerve, and the saphenous nerve. These three nerves innervate the lower leg and foot, providing sensory and motor function. The large sciatic nerve splits just above the knee to form the tibial and common peroneal nerves. The tibial nerve travels down in the posterior region, while the common peroneal nerve runs around the lateral side of the knee and runs down the front of the leg to the foot. Although all these nerves can be affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This Special Issue bridging the gap between science and practice in the promotion of exercise and health and in the scientific assessment, study, and understanding of sports performance, sports injury prevention and treatment, exercise for health as non-surgical and nonpharmacological treatments, rehabilitation techniques, adapted physical activity, drugs in sport, and recommendations for training and nutrition. This Special issue comprises 3 review articles and 16 original research publications from a number of Sports Medicine and Sciences researchers [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Taken together, these articles are…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…This Special Issue bridging the gap between science and practice in the promotion of exercise and health and in the scientific assessment, study, and understanding of sports performance, sports injury prevention and treatment, exercise for health as non-surgical and nonpharmacological treatments, rehabilitation techniques, adapted physical activity, drugs in sport, and recommendations for training and nutrition. This Special issue comprises 3 review articles and 16 original research publications from a number of Sports Medicine and Sciences researchers [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Taken together, these articles are…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…[12] Iatrogenic causes include mainly the lower back spine, hip, and knee surgeries. [1][2][3][4][5][6][8][9][10][11][12][13][16][17][18][19]21,22] Lumbosacral plexopathy can cause peroneal or tibial nerve pathology, weakening or loss of the foot and ankle dorsiflexors resulting in foot deformity, and functional gait impairment with characteristic foot slap during the heel strike and a steppage gait. [18,20] Lumbar spinal nerve root damage and peroneal nerve injury are the most frequent causes of foot drop.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][8][9][10][11][12][13][16][17][18][19]21,22] Lumbosacral plexopathy can cause peroneal or tibial nerve pathology, weakening or loss of the foot and ankle dorsiflexors resulting in foot deformity, and functional gait impairment with characteristic foot slap during the heel strike and a steppage gait. [18,20] Lumbar spinal nerve root damage and peroneal nerve injury are the most frequent causes of foot drop. [4] Bakhsh et al [2] reported that the long-term outcome of lumbar disk surgery was unsatisfactory, and new neurological deficits caused foot drop postoperatively in 8.8% of their patients.…”
Section: Introductionmentioning
confidence: 99%